Comparison of first-line treatment with CHOP versus ICED in patients with peripheral T-cell lymphoma eligible for upfront autologous stem cell transplantation - Kim, Seok Jin; Jo, Jae-Cheol; Yoon, Dok Hyun; Yang, Deok-Hwan; Yoon, Sang Eun; Lee, Gyeong-Won; Kong, Jee Hyun; Park, Yong; Kang, Ka-Won; Lee, Ho-Sup; Oh, Sung Yong; Shin, Ho-Jin; et al. (Frontiers in Oncology, 2023)
Introduction Upfront autologous stem cell transplantation (ASCT) has been recommended for patients who are newly diagnosed with peripheral T-cell lymphoma (PTCL), and CHOP (cyclophosphamide, doxorubicin, vincristine, and prednisone), an anthracycline-based chemotherapy has been the frontline chemotherapy for PTCL. However, it is not clear whether anthracycline-based chemotherapies such as CHOP could be standard induction therapy for PTCL. Methods We conducted a randomized phase II study to compare CHOP with fractionated ifosfamide, carboplatin, etoposide, and dexamethasone (ICED) for patients eligible for ASCT. The primary endpoint was progression-free survival (PFS) and secondary endpoints included objective response rate, overall survival (OS), and safety profiles. Results Patients were randomized into either CHOP (n = 69) or ICED (n = 66), and the characteristics of both arms were not different. PTCL-not otherwise specified (NOS, n = 60) and angioimmunoblastic T-cell lymphoma (AITL, n = 53) were dominant. The objective response rate was not different between CHOP (59.4%) and ICED (56.1%), and the 3-year PFS was not different between CHOP (36.7%) and ICED (33.1%). In AITL patients, CHOP was favored over ICED whereas ICED was associated with more cytopenia and reduced dose intensity. Patients who received upfront ASCT after achieving complete response to CHOP or ICED showed 80% of 3-year OS. Discussion In summary, our study showed no therapeutic difference between CHOP and ICED in terms of response and PFS. Thus, CHOP might remain the reference regimen especially for AITL based on its better outcome in AITL, and upfront ASCT could be recommended as a consolidation of complete response in patients with PTCL.